COHORT EFFECTS IN OLD-AGE COGNITIVE AGING: A STUDY OF SOCIAL CONTEXT IN CHILDHOOD IN 140, 030 OLDER ADULTS. (20th December 2022) - Scott, Stacey; Shawver, Zared; Clouston, Sean; Zhang, Yun; Voll, Stacey; O'Keefe, Patrick; Rodgers, Joeseph; Hofer, Scott M
Abstract: Researchers have reported that later-born cohorts often have higher scores on cognitive tests, potentially indicating that some of the differences normally attributed to cognitive aging may reflect developmental differences. The present study examined the hypotheses that social factors at birth and in early adolescence might partially explain birth cohort effects. This secondary analysis of data collected prospectively as part of four internationally comparable and nationally representative studies of individuals aged 50 and older residing in 17 European countries and the United States (N=140, 030). Cognition was prospectively measured longitudinally 360, 150 observations spanning, on average, 4.27 (SD=5.12) years allowing us to leverage age/cohort variability. Multilevel longitudinal modeling was used incorporated random intercepts and slopes at the country and individual levels to model lifetime cognition while adjusting for contextual factors. Birth cohort was associated with height (B=0.095, SE=0.002, P< 1E-06), episodic memory (B=0.105, SE=0.001, P< 1E-06), and verbal fluency (B=0.217, SE=0.002, P< 1E-06). Approximately 7.72% (95% C.I.=[7.60-7.86]) of participants were exposed to at least two years of famine in childhood, and were born into countries with moderate levels of income inequality. Multivariable adjustment accounted for 15.10-24.96% of birth cohort effects in episodic memory and verbal fluency respectively. Longitudinal modeling revealed that after adjusting for famine, war, income inequality, educational attainment, and height, these factors explained 81.58-63.65% of the birth cohort effect in episodic memory and verbal fluency respectively. Global research has reported that early life factors can have an impact on development, so this study extends this to suggest these factors have a lifelong impact.